(untitled) (Revista Apotheke, 2022)
Art and literature are connected in the experience described in this work to build relationships between weaving texts and textiles. These relationships were sewn through the action of the extension projects “Experiences of shared reading” and “Artisting, making ceramics and a lot more”, from Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS) - Campus Feliz, in partnership with Pedro Hahn library and the municipal schools of Feliz/RS. The aim is to mobilize the aesthetic experience through literary education and art in theoretical-practical propositions that significantly nourish life. The aesthetic and pedagogical workshops were collectively planned and carried out with fifty students from two municipal schools, who experienced aspects of the inventive creation. This process took place through memories and stories which have connected and produced significant experiences, associating literature and art.